Criterion for Ensuring the Effectiveness of the Management of the Global Maritime Industry - Sienko, Olena; Babachenko, Maryna; Chesnokova, Maryna; Karianskyi, Sergey (Dr. Viktor Koval, 2023)
Introduction. The significant dynamic nature of modern geopolitical and military threats sets new requirements for evaluating the criteria effectiveness of solving maritime industry management problems, requires new methodological approaches and mathematical models for evaluating criteria, and determines a new architecture of information systems in the structure of which these approaches and models are implemented. This makes the issue of the analysis of the application of criteria and the development, research, and implementation of such models and systems extremely relevant. Aim and tasks. The purpose of the study is to create a methodological approach to evaluating the criteria that characterize the effectiveness of the management of the maritime industry, with the dynamic change of criteria due to the influence of threats and challenges. Results. A methodological approach has been developed to evaluate the criteria that characterize the effectiveness of the management of the maritime industry based on the model for assessing the convergence of the absolute values of the first derivatives of the criteria over time, which, at short time intervals, can be considered as criteria change trends. It has been established that instead of reducing transportation costs, management switches to the principle of ensuring optimal costs, which leads to an increase in the cost of freight and shock reactions in the sea transportation market. It was established that it is advisable to use the LSCI criterion as an indicator of the negative effect of “local optimization”. After determining the development trends of the criteria, their evaluation as well as the assessment of their convergence were carried out, which became the basis for proposing directions for improving the efficiency of maritime industry management. Conclusions. The developed methodological approach and the mathematical model of its implementation make it possible to conduct both quantitative and qualitative analyses of the effectiveness of management of the maritime industry. To increase the efficiency of management, it is proposed: to integrate port community systems; to increase the stability of the port infrastructure so that it can function in crisis conditions; to achieve coordination of management actions at all levels; to avoid “local optimization” and introduce integral optimization; to respond not only to direct threats but also to detect the cascading effects of threats.